Pengaruh Tangible, Reliability, Responsiveness, Assurance Dan Emphaty Terhadap Kepuasan Nasabah Bank Jabar Banten Di Surabaya - Thyophoida W.S. Panjaitan (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2011)
If the banks want to continue to exist it is necessary to create a business concept that is still running. One of the concepts in these activities is the concept of marketing. Success or failure of business activities depends on how the marketing system, so it is important for banks to understand the